1995
DOI: 10.1128/jb.177.13.3752-3757.1995
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of nonpathogenic Agrobacterium tumefaciens mutants arising in crown gall tumors

Abstract: Little is known about the effect of the host on the genetic stability of bacterial plant pathogens. Crown gall, a plant disease caused by Agrobacterium tumefaciens, may represent a useful model to study this effect. Indeed, our previous observations on the natural occurrence and origin of nonpathogenic agrobacteria suggest that the host plant might induce loss of pathogenicity in populations of A. tumefaciens. Here we report that five different A. tumefaciens strains initially isolated from apple tumors produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 18 publications
1
33
0
3
Order By: Relevance
“…67,2003 AGROBACTERIUM-MEDIATED PLANT TRANSFORMATION 27 on May 9, 2018 by guest http://mmbr.asm.org/ have been revealed by various assays. Thus, rat1 (encoding an arabinogalactan protein) and rat3 (probably encoding a plant cell wall protein) are involved in bacterial attachment to roots (23). Other rat genes that may affect cell wall structure include a xylan synthase (rat4 [232]) and a ␤-expansin (A. Kaiser, A. Kopecki, Y. Zhu, and S. B. Gelvin, unpublished data).…”
Section: Forward Genetic Screening To Identify Plant Genes Involved Imentioning
confidence: 99%
See 1 more Smart Citation
“…67,2003 AGROBACTERIUM-MEDIATED PLANT TRANSFORMATION 27 on May 9, 2018 by guest http://mmbr.asm.org/ have been revealed by various assays. Thus, rat1 (encoding an arabinogalactan protein) and rat3 (probably encoding a plant cell wall protein) are involved in bacterial attachment to roots (23). Other rat genes that may affect cell wall structure include a xylan synthase (rat4 [232]) and a ␤-expansin (A. Kaiser, A. Kopecki, Y. Zhu, and S. B. Gelvin, unpublished data).…”
Section: Forward Genetic Screening To Identify Plant Genes Involved Imentioning
confidence: 99%
“…However, the situation is likely to be more complex. Belanger et al (23) showed that individual virA genes may be particularly suited to function in certain genetic backgrounds, and Krishnamohan et al (183) recently demonstrated that Ti plasmids may have evolved to optimize specific combinations of virA, virG, and vir boxes. As noted above, the Ti-plasmid pTiBo542 in the C58 chromosomal background is hypervirulent on certain legume species, possibly because of the associated virG gene (41, 146, 159), but not in its native Bo542 chromosomal background (143).…”
Section: Virulence Gene Expression and Plant Transformationmentioning
confidence: 99%
“…Напри мер, при инфицировании хозяина не отдельными клет ками, а их группами (проникновение цианобактерий в коралловидные корни саговников или в листовые же лезы Gunnera) этот процесс может быть описан с ис пользованием не стохастических, а более простых де терминистических подходов. При моделировании попу ляционной динамики агробактерий следует учитывать появление генетически измененных вариантов не толь ко в почве, но и в организме хозяина, где могут индуци роваться мутации [10] или перенос генов [7].…”
Section: Discussionunclassified
“…Previous studies had shown that growth of strains D10B/87 and C58 was inhibited under conditions of vir gene induction, this inhibition favoring the selection of avirulent mutants which had become insensitive to the phenolic vir gene inducers (3,15). Because the transconjugant CB100 exhibited a defect in vir gene induction at acetosyringone concentrations of up to 100 M (see above), it appeared possible that this transconjugant would not produce avirulent mutants under FIG.…”
Section: Examination Of Vir Gene Induction and Oncogenicity In Differmentioning
confidence: 99%